Emerging and Re-emerging Microbial Pathogens: Global Challenges and Public Health Implications - AL-Hilali, Rusul Hamza; Zainab Jawad Abo-Tbeak (American Journal of Biology and Natural Sciences, 2026)
Emerging and re-emerging microbial pathogens remain a significant global health threat fuelled by rapid urbanization, climate change, population movement, environmental disruption, antimicrobial resistance and weaknesses in health systems. They may be newly introduced by humans or have recently been brought into the human population and include pathogenic bacteria, viruses, fungi and parasites that cause outbreaks resulting in substantial morbidity, mortality and socioeconomic expense. They arise from intricate interplays of human behavior, changes in ecosystems, animal reservoirs and evolutionary jumps of pathogens. The COVID-19 pandemic, again highlights how a new infectious agent can rapidly cross frontiers, overwhelm health services everywhere and expose inequities in the capacity to prepare for and respond to such threats. This article provides a review of the major types of emerging and re-emerging microbial pathogens, their primary drivers and their public health implications. Furthermore, it explores the importance of surveillance systems, laboratory diagnostics, genomic technologies, infection prevention measures, vaccination campaigns to decrease transmission and antimicrobial stewardship and risk communication to contain effects. It also emphasizes ongoing issues in low- and middle-income countries, driven by limited resources and delayed detection as well as difficulty in accessing health care intensifying vulnerability to outbreaks. This perspective emphasizes the One Health approach as a critical framework for understanding pathogen emergence at the human-animal-environment interface. Preparedness is further strengthened through global efforts, investment in public health infrastructure and interdisciplinary collaboration. Future efforts will need to incorporate early warning systems, epidemiological data driven outbreak prediction, and a bias for diagnostic access and countermeasure equity. For this reason, knowledge of the changing epidemiology of threats to human health from microbes will be central to preserving population health and strengthening resilience in times of future epidemics and pandemics.